Analysis of teaching factory (TEFA) implementation in making Pait village profile video - Wibowo, Ary Agung; Prasetya, Luhur Adi; Haq, Salsabila Thifal Nabil; Rofiudin, Amir; Hendranawan, Rian Syahmulloh; Ichwanto, Muhammad Aris; Isnandar, Isnandar; Mariana, Rina Rifqie; Martin, Denny; Suhendri, Suhendri (Univeritas Papua, 2025)
This research aims to analyze collaboration through teaching factory (TEFA) in making village profile videos as a practice-based learning method involving students, college students, teachers, and the community. The research method used is a case study approach with data collection techniques in the form of in-depth interviews, participatory observation, and document analysis. The results showed that students successfully improved technical skills, such as camera operation and video editing, as well as soft skills, including teamwork, communication, and problem solving. For students, the project served as a professional development platform in mentoring, team management, and leadership. Teachers act as facilitators, while students become mentors who help students put theory into practice. This collaboration reflects the application of Gray's collaboration theory and Vygotsky's social constructivism through the process of scaffolding and social interaction. In addition, the resulting profile videos positively impacted the village community by promoting local potential and increasing community-based economic awareness. This research proves that TEFA is effective in linking theory and practice and directly contributes to skills development and local economic development.